If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -8 = 12y + -8 Reorder the terms: -8 + 7y = 12y + -8 Reorder the terms: -8 + 7y = -8 + 12y Add '8' to each side of the equation. -8 + 8 + 7y = -8 + 8 + 12y Combine like terms: -8 + 8 = 0 0 + 7y = -8 + 8 + 12y 7y = -8 + 8 + 12y Combine like terms: -8 + 8 = 0 7y = 0 + 12y 7y = 12y Solving 7y = 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. 7y + -12y = 12y + -12y Combine like terms: 7y + -12y = -5y -5y = 12y + -12y Combine like terms: 12y + -12y = 0 -5y = 0 Divide each side by '-5'. y = 0 Simplifying y = 0
| 5v^2-5v/1-v | | -14x-6y=18 | | 6t-3+2t=29 | | -6(x+3)+4x+7=6x+8 | | T=4U/E | | -3-p=5p+21 | | X^2-3ax+2a^2+3a-9=0 | | 5a+b=cfora | | T=AB-2 | | 9x-8+9x=7x+16 | | -x+4x+6=14-2 | | 58a+b=cfora | | 13x-3=5x | | 2b-3+6-8=1-b | | x/(x+1)+x/(x-1)=0 | | 2x/5+3=101/2 | | 4m-y=nform | | 12+4x=8x-8 | | 1/2(8-6h)=5 | | 3x^2-12x+24y-48=0 | | 6-4x=7x-9x+4+2 | | C=15f+8h+5p | | 27x-2+47=180 | | 4z+6z=10 | | 27x-2=47 | | 4(x-3)+2=26 | | 7m+n=2forn | | 16x-8=14x+8 | | -3-(2-3x)=2x-(5-x) | | (3x-c)-5=x-7 | | 13-2n=-37 | | a+b(x-y)=cforx |